2016
DOI: 10.1308/rcsann.2016.0052
|View full text |Cite
|
Sign up to set email alerts
|

The utility of repeat ultrasound imaging in the follow-up of metal-on-metal hip arthroplasty patients

Abstract: Repeat ultrasound in MoMHA patients demonstrated that findings frequently progress in the short-term. Therefore, regular surveillance of MoMHA patients is important, with ultrasound representing an effective investigation for identifying the development and progression of lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“… 2016 , Matharu et al. 2016a ), and predictors of poor outcomes following ARMD revision (De Smet et al. 2011 , Liddle et al.…”
Section: Resultsmentioning
confidence: 99%
“… 2016 , Matharu et al. 2016a ), and predictors of poor outcomes following ARMD revision (De Smet et al. 2011 , Liddle et al.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, periprosthetic area need to be carefully assessed in MOM THA cases in image screening. Several previous studies have demonstrated the e cacy of ultrasonography in diagnosing ARMD, but no prior report has proposed a ultrasonographic screening protocol for periprosthetic area in HRA patients (7)(8)(9)14). Hence, the major goal of our present study was to assess the accuracy of ultrasonography for this purpose using a standardized protocol that focused on the periprosthetic muscles in HRA patients and a comparison with MRI ndings.…”
Section: Discussionmentioning
confidence: 96%
“…Measurements of metal ions are a recommended screening method for possible ARMD, but can be prohibitively costly if not covered by national health insurance (10). MRI or CT scans are universal imaging modalities for the screening of pseudotumors (7)(8)(9)(11)(12)(13)(14) but implant halation prevents the careful assessment of periprosthetic soft tissues with these methods, which is problematic in the case of implant-related complications that mainly originate in these tissues. Recent improvements to the resolution in ultrasonography have enabled a more precise evaluation of various parts of body and the utility of this approach has been demonstrated for the screening of ARMD in MOMTHA patients (7)(8)(9)14).…”
Section: Introductionmentioning
confidence: 99%
“… 2013 , Matharu et al. 2016c ). It must be acknowledged that the prevalence of ARMD in MoMHAs on both ultrasound and MARS-MRI has been much higher (up to 61%) (Kwon et al.…”
Section: Hip Imagingmentioning
confidence: 99%
“… 2015b , Matharu et al. 2016c ). Hip abductor atrophy has frequently been reported in MoMHAs and can progress over 1 year, with some suggesting atrophy may be a precursor to irreversible muscle destruction (Berber et al.…”
Section: Hip Imagingmentioning
confidence: 99%